2014
DOI: 10.3791/51898
|View full text |Cite
|
Sign up to set email alerts
|

A Procedure to Observe Context-induced Renewal of Pavlovian-conditioned Alcohol-seeking Behavior in Rats

Abstract: Environmental contexts in which drugs of abuse are consumed can trigger craving, a subjective Pavlovian-conditioned response that can facilitate drug-seeking behavior and prompt relapse in abstinent drug users. We have developed a procedure to study the behavioral and neural processes that mediate the impact of context on alcohol-seeking behavior in rats. Following acclimation to the taste and pharmacological effects of 15% ethanol in the home cage, male Long-Evans rats receive Pavlovian discrimination trainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Even though the latter have repeatedly been the subject of investigation, there is no general consensus on whether or not AUD patients show general and uniform changes in S-R binding: On the one hand, it has repeatedly been shown that AUD patients display enhanced associations and pavlovian instrumental transfer for alcohol-associated stimuli. 55,56 With respect to neutral (ie, nonalcohol-related) stimulus processing, there are however much fewer findings, and they tend to rather point into the opposite direction. In line with this, individuals with AUD seem to show reduced proactive inference 57 and potentially reduced attentional processing of environmental stimuli.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though the latter have repeatedly been the subject of investigation, there is no general consensus on whether or not AUD patients show general and uniform changes in S-R binding: On the one hand, it has repeatedly been shown that AUD patients display enhanced associations and pavlovian instrumental transfer for alcohol-associated stimuli. 55,56 With respect to neutral (ie, nonalcohol-related) stimulus processing, there are however much fewer findings, and they tend to rather point into the opposite direction. In line with this, individuals with AUD seem to show reduced proactive inference 57 and potentially reduced attentional processing of environmental stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, such investigations would include different groups, like moderate drinkers, regular binge‐drinkers, and AUD patients. Even though the latter have repeatedly been the subject of investigation, there is no general consensus on whether or not AUD patients show general and uniform changes in S‐R binding: On the one hand, it has repeatedly been shown that AUD patients display enhanced associations and pavlovian instrumental transfer for alcohol‐associated stimuli 55–56 . With respect to neutral (ie, nonalcohol‐related) stimulus processing, there are however much fewer findings, and they tend to rather point into the opposite direction.…”
Section: Discussionmentioning
confidence: 99%
“…Every other day (i.e. Monday, Wednesday, Friday) rats were given 24-hour access to 15% EtOH and water via a 100 ml graduated cylinder and 500 ml bottle that were placed onto the home cage lids (Maddux, Lacroix, & Chaudhri, 2014;Simms et al, 2008;Wise, 1973). On Tuesday, Thursday, Saturday, and Sunday, EtOH cylinders were replaced with water bottles (procedure adapted from Sparks, Sciascia, Ayorech, & Chaudhri, 2014).…”
Section: Home-cage Ethanol Exposurementioning
confidence: 99%